Bycatch mitigation in the West Greenland lumpfish (Cyclopterus lumpus) fishery using modified gillnets. Issue 4 (5th April 2023) - Post, Søren; Merkel, Flemming; Bak-Jensen, Zita; Koch, Christoffer; Hedeholm, Rasmus Berg
Abstract : Bycatch in gillnets is a global issue and mitigation measures that balance target species catch rates, bycatch reduction and fisher support are scarce. In the North Atlantic lumpfish fisheries, bycatch includes marine mammals and seabirds, and there are no permanent technical initiatives to reduce the bycatch. In the West Greenland fishery, common eider bycatch is several thousand individuals annually. We explored if bycatch in this fishery could be reduced by modifying standard lumpfish gillnets by adding a 45 cm high small-meshed net panel to the bottom part of the net. We tested the nets in combination with standard nets and estimated catch rates in a controlled setting in 2021 and in the commercial fishery in 2022. The modified nets had a 71% reduced bycatch rate for common eider and a 25% reduced catch rate for female lumpfish. A combination of the panel and increased seaweed entanglement was the most likely explanation for the effect. In addition to the effect of the net modification, the common eider bycatch decreased significantly during the season, and we recommend studying the net effect further and exploring the option of postponing the fishing season as a simpler way of reducing bycatch.